Интерсемиотические отношения в переводе культурного иного (на примере фильма „Ностальгия” Андрея Тарковского) - Mocarz-Kleindienst, Maria (Studia Rossica Posnaniensia, 2019)
The title nostalgia in Andrei Tarkovsky’s film is evoked by the Russian writer’s longing for his family and homeland. It is activated in his contact with another culture, in this case with Italian culture. This paper attempts to provide an analysis of the mechanisms used by the director to make a projection of this emotional state and to portray it in the film. A number of intersemiotic relations among visual, verbal and sound codes were analysed. The following relations were identified: complementarity, parallelism and contradiction. The provided examples show the significance of the visual code as an indicator of cultural otherness. They also prove the diversity of stylistic devices used for transposing emotional states to the physical world.